ADVANTAGES OF IMPLEMENTING NEW STANDARDS BASED ON ESG PRINCIPLES IN INDUSTRIAL ENTERPRISES (World Economics and Finance Bulletin, 2025)
This paper explores the advantages of implementing new standards in industrial enterprises based on ESG (Environmental, Social and Governance) principles. Drawing on international practices, it is demonstrated that adopting ESG approaches contributes to sustainable development, ensures environmental safety, enhances social responsibility and increases investor confidence. The integration of ESG standards leads to improved production efficiency and strengthens the competitive position of industrial enterprises in the market. The study also highlights potential challenges in ESG implementation and proposes practical solutions to overcome them. In the context of the rapid development of the global economy, promoting corporate economic development while taking into account sustainable development has gradually become the focus of attention of countries around the world. The ESG performance reflects the differences in the assessment of enterprises’ sustainable development potential by capital market information intermediaries. These differences affect the internal governance and external financing of enterprises, thereby influencing corporate green innovation